TOKEN EKONOMI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Dewi Mahastuti; Dwi Sarwindah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Learning motivation is one of the factors that influence success in student learning.Motivation is the driving force in doing something for optimum success. This studyaims to see the effect of giving the Economic Token method (positivereinforcement) to increase the achievement motivation of elementary schoolstudents. This study used a single subject, namely the fifth grade elementary schoolchildren with the age of 11 years. The assessment methods used are observation,interviews and psychological tests. Giving economic tokens here by giving rewardsin the form of praise and gifts of goods that are highly desired by the subject.Rewards will be given when the subject can carry out the given task properly andaccording to the target. If it does not work, it is considered a failure and asked totry again. The data obtained were analyzed descriptively by looking at changes intheir learning motivation, based on their learning outcomes and changes inbehavior on the behavior check list.